The rise of a new anchor currency in RCEP? A tale of three currencies - Dong Guo; Peng Zhou (Cardiff University, Cardiff Business School, 2021)
We propose a flow-based criterion (intensity of use) and a stock-based criterion (stability of value) for choosing an anchor currency. This conceptual framework is applied to analyzing the RCEP region. According to the estimated TVP-VAR model, the influence of the US dollar in the region was weakened during the global financial crisis and the COVID pandemic, creating an opportunity for both Chinese Yuan and Japanese Yento compete for the anchor currency. In terms of the intensity criterion, China accounts for the largest share in the regional share, but Yen seems to havean upper hand in the stability criterion. The sophisticated cooperative-competitive relationship between China and Japan may prolong the birth of a new anchor currency. Before then, US dollar still holds the role and the RCEP regional trade is subject to excessive volatility.
Keywords: F13; F33; F45; 330; RCEP; TVP-VAR; Anchor Currency; Internationalization